Safari Dakwah Sebagai Media Pembentukan Karakter Bagi Osis Mts Al Yakin Pungpungan - Sahri sahri; Moh. Miftahul Choiri (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
This article examines the tradition of Safari Da'wah as a character formation medium for OSIS MTs Al-Yakin Pungpungan. Safari Da'wah is a da'wah activity going from house to house members of the OSIS held every two weeks. This activity is one of the routine agenda undertaken by members of OSIS and accompanying teachers. No other purpose is to brief the character of the members of OSIS. For example by growing the soul of leadership, and then discipline, obey the rules and so forth. This activity was originally the idea of the principal, the teachers and the entire school community. Starting from idea, then applied and running until now well. This activity is evaluated at all times, selected activities that are related to the growth of children's character. The content of these activities is the reading of prayers and religious speech that speakers are taken from students in turn. Hopefully this Safari Dakwah activities can be carried out consistently on MTs Al Yakin or on other MTs.